The role of Penza church historical, archaeological and statistical committee in shaping public interest in provincial everyday life (based on the materials of the Penza diocesan gazette) - Sergey Viktorovich (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2023)
The article analyzes the activities of the Penza Church Historical, Archaeological and Statistical Committee for the Preservation of the History and Description of the Daily Life of Cities, Villages and Parishes of the Penza Diocese. As a source for studying this problem, the materials of the «Penza diocesan gazette» (1866-1917) were used, on the pages of which articles and essays of members of the Committee were published. Documents on the organization of the Penza Church Historical, Archaeological and Statistical Committee, as well as numerous publications of its members, have been studied. The reasons for the organization of the Committee, its place and role in the system of historical and archival institutions of the Penza province were investigated; organizational structure and composition; quantitative and qualitative analysis of the results of the activity was carried out; a description of the clergy'perception of parish life in the cities and villages of the Penza diocese, as well as the peculiarities of the class organization of Russian society in the era of modernization, using the example of the peasantry and clergy, was given. The historical, archaeological and statistical committee acted at the Penza Theological Seminary from February 14 (27), 1902 until 1918. This body played a prominent role in shaping public interest in local history and provincial everyday life. The Orthodox clergy was involved in expeditionary research of the provincial "living history," not recorded in historical documents, but transmitted from generation to generation according to oral tradition. The description of the modern state of the parishes was carried out, in modern terms, through the "included observation" of the priests themselves. The activities of the Committee significantly complemented the research results of the Provincial Statistical Committee. The analysis of publications in the Penza diocesan gazette convinces that representatives of the Orthodox clergy, having the initial goal of collecting and summarizing information on the history of the Russian Church in the Penza Territory, describing the history of settlements, churches, monasteries and parishes, discovered crisis bias in the development of the entire Russian society. While describing the daily life of the province, it turned out that the clergy and peasantry underwent unfavorable historical circumstances. The acute shortage of arable land became widespread and everyday phenomena; the insufficient level of development of education and medicine, as well as technical equipment of peasant farms; lack of productive land-cultivation practices, mass poverty, the low crop capacity and recurrent hunger; forced migration in the conditions of "latrine" industries, etc. The consequences of the above phenomena were the extinction of the cultural traditions of the peasant world, the rupture of stable social ties and crisis phenomena in the religious and moral state of society. The clergy fully shared the hardships of the daily life of the peasantry, experiencing a poor financial situation. Essays on the history of villages and parishes, compiled by members of the Committee, were a signal for the deep reform of society.